PENGARUH TERPAAN BERITA KASUS PINJAMAN ONLINE DAN TINGKAT LITERASI KEUANGAN TERHADAP KEPUTUSAN MENGGUNAKAN PINJAMAN ONLINE - Pemelia, Ehma; Luqman, Yanuar; Qurrota Ayun, Primada (Interaksi Online, 2024)
The decision to use online lending is on the rise. The number of borrower accounts and the value of outstanding loans continue to increase. But, at the same time, news of online lending cases has led to a negative perception of online loans. In addition, a person's decision to use or purchase a product is based on knowledge of the product. However, the level of financial literacy in society is still relatively low. This research aims to determine the influence of news exposure of online lending cases and the level of financial literacy on the decision to use online lending. Therefore, a quantitative approach with simple linear regression analysis was used to test the hypothesis. The theories used are Mass Media Effect Theory and Social Cognitive Theory. This study uses a sample of fifty respondents. The sample was selected using purposive sampling techniques with the respondent characteristics being male or female aged raging from 19-34 years, residing in Semarang City—exposed to news about online lending cases through mass media, and having used online lending. The simple linear regression test results that there is an influence of news exposure of online lending cases on the decision to use online lending. This result is indicated by a significance value of 0.002 (<0.05) with a regression coefficient of 0.179 (17.9%). The next result is that the decision to use online lending does not affected the level of financial literacy. This result is shown by a significance value of 0.57 (>0.05).